The use of alternative coloring variations to mitotic observations of shallots using the squash method - Tirtasari, Ni Luh; Saputri, Luthfi Hanum; Dewi, Nur Kusuma; Siswanti, Siswanti (STKIP Persada Khatulistiwa Sintang, 2024)
Practicum cannot be carried out due to limited facilities and infrastructure such as dyes for observation of mitotic cell chromosomes in onions. Alternative dyes that can be obtained from nature can be explored. The purpose of this study was to obtain preparation of the mitotic division process in various onion root cells using alternative dyes using dyes from dragon fruit peel and turi flower. In obtaining the right preparation using the squash method. Data were obtained using observation sheets that observed each variation of the material. The instrument used in this study is a valid observation sheet. The results showed that the coloring of the preparation using dragon fruit skin and turi flowers was successful and clear coloring results were obtained. Coloring in practicum activities using turi flowers is better than dragon fruit coloring. Natural dyes from dragon fruit peel and turi flower can be used as alternative dyes in the squash method to observe onion root mitosis, replacing synthetic dyes.Â